Analisis Rantai Pasok Jamur Tiram di UMKM Sidimpuan Hiratake Mushroom Dalam Memenuhi Permintaan - Ariffien, Afferdhy; Ritonga, Anggita Rahmad; Siswanto, Budi Nur (Politeknik ATI Padang, 2024)
Oyster mushrooms, Pleurotus ostreatus, are a type of edible wood mushroom. MSME Sidimpuan Hiratake Mushroom have customer, a family restauran. In order to meet consumer demand with quality and quantity requirements, MSME had issues such as inability to fulfill demand due to insufficient production capacity, and occurrence of returns, where both of these continue to increase. Purpose of this study is to explain the process of supply chain, to find out the actual performance, and to provide some suggestions for improvements to the performance of supply chain. The process flows analyzed in this supply chain are product, information and financial. The product produced by partner farmers is fresh oyster mushrooms, the products that will be sent to restaurant are oyster mushrooms that have been weighed, cleaned and packaged. This research method is qualitative and quantitative. The results of analysis with food supply chain network show that the process flow in the supply chain has been going well. The operational performance measurement results were measured using several supply chain operation reference metrics, that the operational performance of the supply chain cannot be said to be perfect overall. To measure marketing performance, the farmer's share value obtained by partner farmers is 58.3% and the marketing margin for MSME is Rp.5.000. The results of 5 why's analysis, inability to fulfill restaurant's demand was caused due to several things including variations in the growth process as well as limited resources of farmers. Returns are caused by differences in quality control standards and qualifications between restaurant and MSME.